Factor V Leiden and factor II G20210A mutations in patients with recurrent abortion - Souza, S. S.; Ferriani, R. A.; Pontes, Anaglória [UNESP]; Zago, M. A.; Franco, R. F. (My University, 1999)
Recurrent abortion (RA) represents an intriguing problem in obstetric practice in which genetic and acquired factors may play a role. In the present investigation we sought to assess the possibility that inherited thrombophilia might determine the risk of RA. We therefore investigated the prevalence of two genetic abnormalities frequently associated with venous thrombosis [factor V Leiden (FVL) and factor II G20210A] in 56 patients with primary or secondary abortion and in 384 healthy control women. Polymerase chain reaction amplification followed by digestion with the restriction enzymes MnlI and HindIII was used to define the FVL and FII G20210A genotypes respectively. FVL was found in 4/56 patients (7.1%) and in 6/384 controls (1.6%), yielding an odds ratio (OR) for RA related to FVL of 4.9 [95% confidence interval (CI): 1.3-17.8]. FII G20210A was detected in 2/56 (3.6%) patients and in 4/384 (1%) controls (OR for RA: 3.5, CI: 0.6-19.7). In conclusion, FVL and FII G20210A mutations in patients with RA were more prevalent in comparison with controls. These data support a role for both mutations as determinants of the risk of RA and strengthen the notion that thrombophilia plays a role in this clinical entity.
Keywords: Factor II G20210A; Factor V Leiden; Recurrent abortion; Risk factor; Thrombophilia; blood clotting factor 5; mutant protein; prothrombin; restriction endonuclease; adult; controlled study; female; gene mutation; genotype; human; major clinical study; polymerase chain reaction; prevalence; recurrent abortion; risk; thrombophilia; vein thrombosis; Abortion, Habitual; Adult; Case-Control Studies; Factor V; Female; Humans; Mutation; Odds Ratio; Polymerase Chain Reaction; Pregnancy; Prothrombin; Risk Factors